2009
DOI: 10.1016/j.compgeo.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pile settlement using artificial neural networks based on standard penetration test data

Abstract: In recent years artificial neural networks (ANNs) have been applied to many geotechnical engineering problems with some degree of success. With respect to the design of pile foundations, accurate prediction of pile settlement is necessary to ensure appropriate structural and serviceability performance. In this paper, an ANN model is developed for predicting pile settlement based on standard penetration test (SPT) data. Approximately 1,000 data sets, obtained from the published literature, are used to develop t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…Most traditional pile bearing capacity determination methods included the following parameters: pile geometry, pile material properties, and soil properties [4,5]. The depth of the water table was not included in this study, as it is believed that the effect is already accounted in the SPT blow counts [43]. Since the bearing capacity of piles depended on the soil compressibility and the SPT was one of the most commonly used tests in practice (indicating the in situ compressibility of soils), the SPT blow count/300 mm (N) along the embedded length of the pile was used as a measure of soil compressibility.…”
Section: Data Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Most traditional pile bearing capacity determination methods included the following parameters: pile geometry, pile material properties, and soil properties [4,5]. The depth of the water table was not included in this study, as it is believed that the effect is already accounted in the SPT blow counts [43]. Since the bearing capacity of piles depended on the soil compressibility and the SPT was one of the most commonly used tests in practice (indicating the in situ compressibility of soils), the SPT blow count/300 mm (N) along the embedded length of the pile was used as a measure of soil compressibility.…”
Section: Data Preparationmentioning
confidence: 99%
“…Nawari et al [42] developed an ANN algorithm to predict the deflection of drilled shafts based on SPT data and the shaft geometry. In addition, Pooya et al [43] developed a model to predict the pile settlement using ANN, based on SPT data using 12 input factors. Last but not least, Momeni et al [44] presented an ANN model to predict the shaft and tip resistance of concrete piles.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding rock-socketed piles, numerous investigators [6,7], have shown that the uniaxial compressive strength (UCS) of the rocks has a direct relationship with the pile bearing capacity and its settlement. A popular intelligence system namely the artificial neural network (ANN) was designed and introduced in study by Pooya Nejad et al [8] to predict piling settlement using the standard penetration test data. They utilized nearly 1000 data, collected from previous studies, to develop the ANN models and concluded that the ANN is a powerful technique for solving problem related to pile settlement.…”
Section: Introductionmentioning
confidence: 99%
“…Fan [41] used a logistic model and a Gompertz model to propose a combination forecasting model for the settlement prediction of soft soil foundations, and Li et al [42] employed a combined prediction model based on an improved set pair analysis to predict subgrade settlement. Nejad et al [43] proposed a back propagation neural network model to test the feasibility of predicting pile foundation settlements using artificial neural networks. Oliveira et al [44] proposed a new improved quasi-equal time gray model (QGM (1,1)) prediction model to overcome the shortcomings of traditional non-isochronous models, such as cumbersome calculations and low medium-and short-term prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%